Psychometric properties of the Adverse Childhood Experiences Questionnaire 10 item version (ACE-10) among Hungarian adolescents - Kovács-Tóth, Beáta; Oláh, Barnabás; Kuritárné Szabó, Ildikó; Fekete, Zita (Frontiers in Psychology, 2023)
Introduction Although a number of studies have been conducted since the 1995 initiation of the ACE study to map the effects of adverse childhood experiences, few studies have examined the psychometric properties of the individual versions of the ACE questionnaire. Aims The Adverse Childhood Experiences Questionnaire 10 item version (ACE-10) has only been tested in a single study in an adult population, while its applicability in a particularly vulnerable population, the adolescents, has not been investigated yet. Our present study aims to address this gap in an adolescent sample of 792 subjects from a non-representative general population. Methods Besides demographic data, the Adverse Childhood Experiences Questionnaire 10 item version (ACE-10), the Strengths and Difficulties Questionnaire (SDQ), and the HBSC Symptom Checklist (HBSC-SCL) were employed. Results Our results showed acceptable internal consistency (ɵ = 0.86, α = 0.64) and adequate internal validity (r = 0.28–0.70, p < 0.001). In addition, proper concurrent criterion validity of the questionnaire was found when tested along the SDQ and HBSC-SCL items. Conclusion Our results demonstrate that the ACE-10 is suitable for assessing intrafamilial adverse childhood experiences in adolescents.